Significance of papanicolau smear in STD clinic of a tertiary care teaching hospital - Manipriya, R.; Deepa, K.; Chitra, C. L. (International Journal of Research in Dermatology, 2018)
Background: HPV infection is one of the common STI’s in females with a majority of patients being asymptomatic and sub-clinical. It is often associated with STI’s and can be a great source of morbidity to patients. Pap smear is one of the effective screening tests for genital HPV infections and HPV induced neoplasia. The aim of the study was to assess the epithelial abnormalities and associated STI’s in study group using Pap smear. Methods: 500 female patients above the age of 19 years with vaginal sexual exposure were evaluated with the history, clinical examination, and genital speculum examination, ELISA for HIV and Pap smears. Results: Among the total 500 pap smears, the normal study was found in 148 pap smears (29.6%), abnormal pap smear results in 46 smears (9.2%) and inflammatory smear was found in 306 smears (61.2%). Among the 306 inflammatory smears, 7.6% smears had predominant monocytes and lymphocyte population, 11.8% smears had neutrophils predominantly. 68.9% showed a mixed population of inflammatory cells. Among the total number of abnormal pap smear study, atypical squamous cells was found in majority that is 33 (6.6%), next was carcinoma 4 (0.8%), high grade and low grade squamous intraepithelial lesions contributed 3 (0.6%) and 6(1.2%) each to the abnormal pap smear study results. Commonest associated STI was bacterial vaginosis. Conclusions: Early screening and detection of dysplasia will reduce the morbidity and mortality associated with carcinoma cervix.